THE EFFECT OF USING CANVA MEDIA ON STUDENTS' LEARNING INTERESTS AND LEARNING OUTCOMES IN THE INDONESIAN LANGUAGE SUBJECT OF GRADE V SD NEGERI SUKASARI 5 KOTA TANGERANG - Mudiani Setiawati; Cecep Anwar Hadi Firdos Santoso; Juhana Juhana (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to determine the effect of using Canva as a learning medium on students' interest and academic performance in Indonesian language subjects at Grade V of SD Negeri Sukasari 5, Tangerang City. The urgency of this study arises from the need for innovative learning media to enhance student motivation and understanding. A quantitative approach was used with a Quasi-Experimental Research design, involving two groups: class Va as the experimental group using Canva and class Vb as the control group with conventional methods. Data were collected through questionnaires and post-tests. Validity tests using SPSS 25 showed that all questionnaire items were valid and reliable (Cronbachâ€™s Alpha = 0.683). The normality test indicated that the data were normally distributed in both groups, while the homogeneity test confirmed the data's uniformity. Multivariate analysis (MANOVA) results indicated significant effects (p < 0.05) across all indicators (Pillaiâ€™s Trace, Wilksâ€™ Lambda, Hotellingâ€™s Trace, Royâ€™s Largest Root), leading to the acceptance of Hâ‚. Findings revealed that Canva significantly improved students' learning interest and academic performance. This study contributes to the development of digital media-based learning strategies to enhance the quality of primary education.